A hasty aesthetic in ‘El Debate’ newspaper between 1910 and 1991: A study on the graphic aspect of the Catholic newspaper before the arrival of Angel Herrera - Puebla Martínez, Belén; González Díez, Laura; Pérez Cuadrado, Pedro (Historia y Comunicación Social, 2018)
In the early Twentieth Century the Spanish press began a period of exponential growth for many reasons, from the colonial disaster of 1898 to technological and political factors that had no direct connection with the sale of newspapers in the first instance, but they would end up being definitive. However, the adventure of launching a new daily paper was not an easy task, and less for a Catholic publication. This paper studies the launch of the newspaper El Debate, in 1910, and focuses on its images and its design during the first 13 months to prove the economic difficulties that happened and the main role of an illustrator from Granada, Adrian Almoguera, in the fact of the graphic aspect of the newspaper.
Keywords: El Debate; Adrián Almoguera; images in newspaper design; illustration.